Low Fe Availability for Photosynthesis of Sea-Ice Algae: Ex situ Incubation of the Ice Diatom Fragilariopsis cylindrus in Low-Fe Sea Ice Using an Ice Tank - Yoshida, Kazuhiro; Seger, Andreas; Corkill, Matthew; Heil, Petra; Karsh, Kristen; McMinn, Andrew; Suzuki, Koji (Frontiers in Marine Science, 2021)
Sea-ice algae play a crucial role in the ecology and biogeochemistry of sea-ice zones. They not only comprise the base of sea-ice ecosystems, but also seed populations of extensive ice-edge blooms during ice melt. Ice algae must rapidly acclimate to dynamic light environments, from the low light under sea ice to high light within open waters. Recently, iron (Fe) deficiency has been reported for diatoms in eastern Antarctic pack ice. Low Fe availability reduces photosynthetic plasticity, leading to reduced ice-algal primary production. We developed a low-Fe ice tank to manipulate Fe availability in sea ice. Over 20 days in the ice tank, the Antarctic ice diatom Fragilariopsis cylindrus was incubated in artificial low-Fe sea ice ([total Fe] = 20 nM) in high light (HL) and low light (LL) conditions. Melted ice was also exposed to intense light to simulate light conditions typical for melting ice in situ. When diatoms were frozen in, the maximum photochemical quantum efficiency of photosystem II (PSII), Fv/Fm, was suppressed by freezing stress. However, the diatoms maintained photosynthetic capability throughout the ice periods with a stable Fv/Fm value and increased photoprotection through non-photochemical quenching (NPQ) via photoprotective xanthophyll cycling (XC) and increased photoprotective carotenoid levels compared to pre-freeze-up. Photoprotection was more pronounced in the HL treatment due to greater light stress. However, the functional absorption cross section of PSII, σPSII, in F. cylindrus consistently increased after freezing, especially in the LL treatment (σPSII > 10 nm2 PSII–1). Our study is the first to report such a large σPSII in ice diatoms at low Fe conditions. When the melted sea ice was exposed to high light, Fv/Fm was suppressed. NPQ and XC were slightly upregulated, but not to values normally observed when Fe is not limiting, which indicates reduced photosynthetic flexibility to adapt to environmental changes during ice melt under low Fe conditions. Although ice algae can optimize their photosynthesis to sea-ice environments, chronic Fe starvation led to less flexibility of photoacclimation, particularly in low light conditions. This may have detrimental consequences for ice algal production and trophic interactions in sea-ice ecosystems if the recent reduction in sea-ice extent continues.